ДЕЯКІ ПРОБЛЕМИ СУЧАСНОГО МУЗИЧНО-ВИКОНАВСЬКОГО МИСТЕЦТВА (Педагогіка вищої та середньої школи, 2007)
The author of article accents attention of the reader to perusal and interpretations o f the musical text of vocal product, problems of a modern musical-performing art as such is lighting.